The Visible Aspect of Things: Towards a Synchronic Reading of Donald Barthelme - Surya Bowyer (European Journal of American Studies)
This essay seeks to address a distinct lacuna in criticism regarding the American author Donald Barthelme, one comprised of two dimensions. First, there is a scarcity of analysis of fragments in works apart from Snow White. Second, almost no attention has been paid to the formal intricacies of Barthelme’s fragments, nor to why their visible aspects might be significant. Arguing that Barthelme is an unusually visually-minded writer, this essay examines the use of fragments in a range of his short stories. A Saussurean framework is used to argue that Barthelme’s writing demands we shift the act of reading away from its diachronic conventions and towards a synchronic approach. I analyze such apparently unremarkable textual aspects as dashes, hyphens, and lists, showing that they are used by Barthelme in a way that demands a visual mode of reading. In questioning the significance of causality, this mode of reading has wider implications insofar as it challenges the typical view that the short story should be approached as a form that is driven by narrative.